Strong Adaptive Culture and Employee Compliance for Successful ISO 31000:2018 Risk Management Implementation - Andiko Tongga; Ellya Niken Prastiwi; MF. Arrozi Adhikara (International Journal of Economics and Management Sciences, 2026)
Healthcare organizations are increasingly required to preserve the sustainability of their institutional values by ensuring high-quality services, operational efficiency, and rigorous adherence to risk governance frameworks. RSUD dr. Chasbullah Abdulmadjid Bekasi City continues to face considerable challenges in this regard, particularly due to the limited internalization of core organizational values, disparities in the cultivation of an adaptive culture, and inconsistent employee compliance with established risk management procedures. These issues highlight the necessity for a leadership paradigm grounded in service, empathy, and empowerment.This study investigates the extent to which servant leadership influences the creation and protection of corporate values, while examining the mediating roles of strong adaptive culture and employee compliance doing the implementation of risk management. Employing a quantitative explanatory survey design, the research collected responses from 153 hospital employees, and data were analyzed through Structural Equation Modeling (SEM) to evaluate both direct and mediated causal pathways among variables.The findings reveal that servant leadership significantly strengthens creation and protection of corporate values, not only through direct influence but also by enhancing cultural adaptability and reinforcing compliant behavior in risk-related practices. Leaders who embody service-oriented principles are shown to cultivate work environments that foster mutual trust, organizational learning, and value-based decision-making.This study contributes meaningful empirical evidence to the discourse on leadership, organizational culture, and compliance within public hospital settings. Institutional strategies should prioritize continuous leadership development and comprehensive risk governance training to secure long-term performance excellence and reputational resilience.